On the Estimation and Use of Feature Reliability Information for Noise Robust Speech Recognition - Leutnant, Volker; Haeb-Umbach, Reinhold (International Conference on Acoustics (NAG/DAGA 2009))
In this paper we present an Uncertainty Decoding rule which exploits feature reliability information and interframe correlation for noise robust speech recognition. The reliability information can be obtained either from conditional Bayesian estimation, where speech and noise feature vectors are tracked jointly, or by augmenting conventional point estimation methods with heuristics about the estimator's reliability. Experimental results on the AURORA2 database demonstrate on the one hand that Uncertainty Decoding improves recognition performance, while on the other hand it is seen that the severe approximations needed to arrive at computationally tractable solutions have their noticable impact on recognition performance.

An analytic derivation of a phase-sensitive observation model for noise robust speech recognition - Leutnant, Volker; Haeb-Umbach, Reinhold (Interspeech 2009)
In this paper we present an analytic derivation of the moments of the phase factor between clean speech and noise cepstral or log-mel-spectral feature vectors. The development shows, among others, that the probability density of the phase factor is of sub-Gaussian nature and that it is independent of the noise type and the signal-to-noise ratio, however dependent on the mel filter bank index. Further we show how to compute the contribution of the phase factor to both the mean and the vari- ance of the noisy speech observation likelihood, which relates the speech and noise feature vectors to those of noisy speech. The resulting phase-sensitive observation model is then used in model-based speech feature enhancement, leading to significant improvements in word accuracy on the AURORA2 database.

A GPS positioning approach exploiting GSM velocity estimates - Peschke, Sven; Bevermeier, Maik; Haeb-Umbach, Reinhold (6th Workshop on Positioning Navigation and Communication (WPNC 2009))
A combination of GPS (global positioning system) and INS (inertial navigation system) is known to provide high precision and highly robust vehicle localization. Notably during times when the GPS signal has a poor quality, e.g. due to the lack of a sufficiently large number of visible satellites, the INS, which may consist of a gyroscope and an odometer, will lead to improved positioning accuracy. In this paper we show how velocity information obtained from GSM (global system for mobile communications) signalling, rather than from a tachometer, can be used together with a gyroscope sensor to support localization in the presence of temporarily unavailable GPS data. We propose a sensor fusion system architecture and present simulation results that show the effectiveness of this approach.
Keywords: cellular radio; distance measurement; global positioning system; Global Positioning System; global system for mobile communications; GPS positioning approach; GSM velocity; gyroscopes; gyroscope sensor; inertial navigation; inertial navigation system; odometer; sensor fusion system architecture; sensors

Verbesserung von GPS-basierter Ortung durch GSM-Geschwindigkeitsschaetzungen - Peschke, Sven; Bevermeier, Maik; Haeb-Umbach, Reinhold (DGON Navigationskonvent 2009)

Approaches to Iterative Speech Feature Enhancement and Recognition - Windmann, Stefan; Haeb-Umbach, Reinhold (IEEE Transactions on Audio, Speech, and Language Processing)
In automatic speech recognition, hidden Markov models (HMMs) are commonly used for speech decoding, while switching linear dynamic models (SLDMs) can be employed for a preceding model-based speech feature enhancement. In this paper, these model types are combined in order to obtain a novel iterative speech feature enhancement and recognition architecture. It is shown that speech feature enhancement with SLDMs can be improved by feeding back information from the HMM to the enhancement stage. Two different feedback structures are derived. In the first, the posteriors of the HMM states are used to control the model probabilities of the SLDMs, while in the second they are employed to directly influence the estimate of the speech feature distribution. Both approaches lead to improvements in recognition accuracy both on the AURORA2 and AURORA4 databases compared to non-iterative speech feature enhancement with SLDMs. It is also shown that a combination with uncertainty decoding further enhances performance.
Keywords: AURORA2 databases; AURORA4 databases; automatic speech recognition; feedback structures; hidden Markov models; HMM; iterative methods; iterative speech feature enhancement; model probabilities; speech decoding; speech enhancement; speech feature distribution; speech recognition; switching linear dynamic models

Parameter Estimation of a State-Space Model of Noise for Robust Speech Recognition - Windmann, Stefan; Haeb-Umbach, Reinhold (IEEE Transactions on Audio, Speech, and Language Processing)
In this paper, parameter estimation of a state-space model of noise or noisy speech cepstra is investigated. A blockwise EM algorithm is derived for the estimation of the state and observation noise covariance from noise-only input data. It is supposed to be used during the offline training mode of a speech recognizer. Further a sequential online EM algorithm is developed to adapt the observation noise covariance on noisy speech cepstra at its input. The estimated parameters are then used in model-based speech feature enhancement for noise-robust automatic speech recognition. Experiments on the AURORA4 database lead to improved recognition results with a linear state model compared to the assumption of stationary noise.
Keywords: AURORA4 database; blockwise EM algorithm; covariance analysis; linear state model; noise covariance; noise-robust automatic speech recognition; noisy speech cepstra; offline training mode; parameter estimation; speech recognition; speech recognition equipment; speech recognizer; state-space methods; state-space model

Simulation of Ad Hoc Routing Protocols using OMNeT++ - Sommer, Christoph; Dietrich, Isabel; Dressler, Falko (Mobile Networks and Applications)

An evaluation of object oriented example programs in introductory programming textbooks - Börstler, Jürgen; S. Hall, Mark; Nordström, Marie; H. Paterson, James; Sanders, Kate; Schulte, Carsten; Thomas, Lynda (SIGCSE Bulletin)

Qualitätssicherung in einer interaktiven und lerneraktivierenden E-Learning-Umgebung - Schulte, Carsten; Tolksdorf, Robert (DeLFI Workshops)

Empirical comparison of objects-first and objects-later - Ehlert, Albrecht; Schulte, Carsten (ICER)

Bridging ICT and CS: educational standards for computer science in lower secondary education - Brinda, Torsten; Puhlmann, Hermann; Schulte, Carsten (ITiCSE)

Unterschiede im Lernerfolg von Schülerinnen und Sch\üern in Abhängigkeit von der zeitlichen Reihenfolge der Themen (OOP-First bzw. OOP-Later) - Ehlert, Albrecht; Schulte, Carsten (INFOS)

Informatik im Kontext (IniK) - Ein integratives Unterrichtskonzept für den Informatikunterricht - Koubek, Jochen; Schulte, Carsten; Schulze, Peter; Witten, Helmut (INFOS)

Dualitätsrekonstruktion als Hilfsmittel zur Entwicklung und Planung von Informatikunterricht - Schulte, Carsten (INFOS)

A simple instance-based approach to multilabel classification using the Mallows model - Cheng, W.; Hüllermeier, Eyke (In Proceedings MLD-2009 1st International Workshop on Learning from Multi-Label Data, Bled, Slovenia)

Learning pattern tree classifiers using a co-evolutionary algorithm - Senge, Robin; Hüllermeier, Eyke (in Proceedings 19th Workshop Computational Intelligence, Dortmund Germany)

Graph-kernels for the comparative analysis of protein active sites - Fober, T.; Mernberger, M.; Moritz, R.; Hüllermeier, Eyke (In Proceedings GCB-2009 German Conference on Bioinformatics Halle (Saale), Germany)

Learning pattern tree classifiers using a co-evolutionary algorithm - Senge, Robin; Hüllermeier, Eyke (In Proceedings Workshop LWA-2009, Lernen-Wissensentdeckung-Adaptivität, Darmstadt, Germany)

Extension and empirical comparison of graph-kernels for the analysis of protein active sites - Fober, T.; Mernberger, M.; Melnikov, Vitaly; Moritz, R.; Hüllermeier, Eyke (In Proceedings Workshop LWA-2009, Lernen-Wissensentdeckung-Adaptivität, Darmstadt, Germany)

Information disclosure by answers to XPath queries - Böttcher, Stefan; Hartel, Rita (Journal of Computer Security)

Efficient construction of multiple geometrical alignments for the comparison of protein binding sites - Fober, T.; Klebe, G.; Hüllermeier, Eyke (in Proceedings ISDA-2009, 9th international Conference on Intelligent Systems Design and Applications, Pisa, Italy)

CSC: Supporting Queries on Compressed Cached XML - Böttcher, Stefan; Hartel, Rita (Database Technologies 2009, Twentieth Australasian Database Conference, ADC 2009)

XML Stream Data Reduction by Shared KST Signatures - Böttcher, Stefan; Hartel, Rita; Messinger, Christian (2009 42nd Hawaii International Conference on System Sciences)

Similarity analysis of protein binding sites: A generalization of the maximum common subgraph measure based on quasi-clique detection - Boukhris, I.; Elouedi, Z.; Fober, T.; Mernberger, M.; Hüllermeier, Eyke (In Proceedings IDA-2009, 9th International Symposium on Intelligent Data Analysis, Pisa / Italy)

Fuzzy modeling of labeled point cloud superposition for the comparison of protein binding sites - Fober, T.; Hüllermeier, Eyke (in Proceedings IFSA / EUSFLAT-2009 World Congress of the Fuzzy Systems Association, Lissabon, Portugal)

A fuzzy variant of the Rand index for comparing clustering structures - Hüllermeier, Eyke; Rifqi, M. (in Proceedings IFSA / EUSFLAT-2009 World Congress of the Fuzzy Systems Association, Lissabon, Portugal)

Methoden und Werkzeuge für einen effizienten Ultraschallsensorentwurf - Henning, Bernd

Trends in ultrasonic transducer design - Henning, Bernd
Ultrasonic sensors are widespread in the process industry for example to measure flow, filling level, density or substance concentration in liquid mixtures today. On one side technically high demands are made to the ultrasonic sensors on the other side the production of the ultrasonic sensors has to be more and more cost-efficient. Today, these two contrary demands only can be met by the use of efficient development tools. This contribution describes the state of technology in the field of the computer-assisted ultrasonic transducer development, however, also shows the limits.

Ultrasonic Sensors for Process Applications - Sensor Design - Henning, Bernd; Rautenberg, Jens; Schröder, Andreas; Unverzagt, Carsten (Proceedings Sensor 2009)
Today, ultrasonic sensor systems are often applied in process technology. For the opening up of new industrial fields of application, such as the non-invasive process tomography, ultrasound sensors are necessary which are stable and adapted optimally under process conditions. Only with such optimized ultrasonic sensors the functionality of the sensor systems can be enlarged decisively with support of a complex measurement data evaluation. This contribution deals especially with the design process.

Computer assisted design of transducers for ultrasonic sensor systems - Henning, Bernd; Rautenberg, Jens; Unverzagt, Carsten; Schröder, Andreas; Olfert, Sergei (Journal of Measurement Science and Technology, MST)
In this contribution, possibilities and methods for computer-assisted design of ultrasound transducers are described. These transducers are essential for an ultrasonic sensor design, e.g. for continuous non-invasive determination of quantities that are important in process technology. To achieve technical reliability and robustness, the precise determination of all acoustic properties of the used sensor materials is of great importance. Problem-oriented modeling, numerical simulation, special optimization algorithms and improved methods for the visualization of propagating waves offer new and promising possibilities for developing ultrasonic transducers with enhanced properties.

Generating of short ultrasonic pulses using active damping - Rautenberg, Jens; Olfert, Sergei; Henning, Bernd
In non-destructive testing (NDT) with ultrasound the emission of short pulses is essentially if the echoes of nearby obstacles should be separated from the emitted signal. In this contribution a new approach is shown how to gene-rate a short ultrasonic pulse using a 3$-$1 composite transdu-cer. Therefore the ceramic bars, which are embedded in a polymer matrix, will be regarded as an exciter for the entire structure. After the pulse excitation the same bars can also be used for active damping to increase the bandwidth of the entire system. The Mason model serves as a basis for the de-scription of the ultrasonic transducer and is extended to the composite structure. The excitation signal is adaptively mo-dified by a suitable signal processing. Therefore the changes of boundary conditions, like the ambient temperature or acoustic impedance of adjacent media are considered.

Interdisciplinary Collaboration in a Visualization Course - Domik, Gitta (Informatics Education Europe IV, November)

Merging chemical and biological space: Structural mapping of enzyme binding pocket space - Weskamp, N.; Hüllermeier, Eyke; Klebe, G. (Proteins)

FURIA: An Algorithm for unordered fuzzy rule induction - Hühn, J.; Hüllermeier, Eyke (Data Mining and Knowledge Discovery)

Why fuzzy decision trees are good rankers - Hüllermeier, Eyke; Vanderlooy, S. (IEEE Transactions on Fuzzy Systems)

Fuzzy operator trees for modeling rating functions - Yi, Y.; Fober, T.; Hüllermeier, Eyke (International Journal of Computational Intelligence and Applications)

Evolutionary construction of multiple graph alignments for the structural analysis of biomolecules - Fober, T.; Mernberger, M.; Klebe, G.; Hüllermeier, Eyke (Bioinformatics)

FR3: A fuzzy rule learner for inducing reliable classifiers - Hühn, J.; Hüllermeier, Eyke (IEEE Transactions on Fuzzy Systems)

Supporting case-based retrieval by similarity skylines: Basic concepts and extensions - Hüllermeier, Eyke; Vladimirskiy, I.; Prados Suarez, B.; Stauch, E. (Künstliche Intelligenz)

Optimal algorithms for page migration in dynamic networks - Bienkowski, Marcin; Byrka, Jaroslaw; Korzeniowski, Miroslaw; Meyer auf der Heide, Friedhelm (Journal of Discrete Algorithms)

Cooperation and coding framework - Biermann, Thorsten; Polgar, Zsolt Alfred; Karl, Holger (Communications Workshops, 2009. ICC Workshops 2009. IEEE International Conference on)

Combining for cooperative WLANs-a reality check based on prototype measurements - Valentin, Stefan; Woldegebreal, Dereje H; Volkhausen, Tobias; Karl, Holger (Communications Workshops, 2009. ICC Workshops 2009. IEEE International Conference on)

Improving network coded cooperation by soft information - Volkhausen, Tobias; Woldegebreal, Dereje H; Karl, Holger (Sensor, Mesh and Ad Hoc Communications and Networks Workshops, 2009. SECON Workshops' 09. 6th Annual IEEE Communications Society Conference on)

On the usefulness of fuzzy sets in data mining - Hüllermeier, Eyke (Views on Fuzzy Sets and Systems from Different Perspectives: Philosophy and Logic, Criticisms and Applications)

Statistics-based ID management for load balancing in structured P2P networks - Warneke, Daniel; Dannewitz, Christian (2009 IEEE 34th Conference on Local Computer Networks)

Decision tree and instance-based learning for label ranking - Cheng, W.; Hühn, J.; Hüllermeier, Eyke (in Proceedings ICML-2009, 26th International Conference on Machine Learning, Montreal, Canada)

Binary decomposition methods for multipartite ranking - Fürnkranz, J.; Hüllermeier, Eyke; Vanderlooy, S. (In Proceedings ECML/PKDD-2009, European Conference on Machine Learning and Principles and Knowledge Discovery in Databases, Bled Sloveniaery in Databases, Bled, Slovenia)

A new instance-based label ranking approach using the Mallows model. In Advances in Neural Networks - Cheng, W.; Hüllermeier, Eyke (in Proceedings 6th International Symposium on Neural Networks, Wuhan, China)

A Multithreaded Framework for Sequential Monte Carlo Methods on CPU/FPGA Platforms - Happe, Markus; Lübbers, Enno; Platzner, Marco (Proceedings of the International Workshop on Applied Reconfigurable Computing (ARC))

Towards Models for Many-Cores: The Case for the Reconfigurable Mesh - Giefers, Heiner; Platzner, Marco (Proceedings of the Workshop on Many-Cores, International Conference on Architecture of Computing Systems (ARCS))

ARMLang: A Language and Compiler for Programming Reconfigurable Mesh Many-Cores - Giefers, Heiner; Platzner, Marco (Reconfigurable Architectures Workshop (RAW), Proceedings of the International Parallel and Distributed Processing Symposium)

Cooperative Multithreading in Dynamically Reconfigurable Systems - Lübbers, Enno; Platzner, Marco (Proceedings of the 19th International Workshop on Field Programmable Logic and Applications (FPL))

Program-driven Fine-grained Power Management for the Reconfigurable Mesh - Giefers, Heiner; Platzner, Marco (Proceedings of the 19th International Workshop on Field Programmable Logic and Applications (FPL))

An adaptive Sequential Monte Carlo framework with runtime HW/SW repartitioning - Happe, Markus; Lübbers, Enno; Platzner, Marco (Proceedings of the 2009 International Conference on Field-Programmable Technology (FPT))

Proof-carrying Hardware: Towards Runtime Verification of Reconfigurable Modules - Drzevitzky, Stephanie; Kastens, Uwe; Platzner, Marco (Proceedings of the International Conference on ReConFigurable Computing and FPGAs (ReConFig))

Semi-Digital Interleaved PFC Control with Optimized Light Load Efficiency - Grote, Tobias; Figge, FHeiko; Fröhleke, Norbert; Beulen, Winfried; Schafmeister, Frank; Ide, Peter; Böcker, Joachim (Proc. 24th IEEE Applied Power Electronics Conference (APEC))

Adaptive Digital Slope Compensation for Peak Current Mode Control - Grote, Tobias; Schafmeister, Frank; Figge, Heiko; Fröhleke, Norbert; Ide, Peter; Böcker, Joachim (Proc. IEEE Energy Conversion Congress and Exposition (ECCE))

Verfahren zur Nutzung des ausgangsseitigen Blindstromes eines indirekten dreiphasen-Matrixkonverters zur Erzeugung von Eingangsblindstrom - Schafmeister, Frank; Kolar, Johann

Energy transfer via linear doubly-fed motor in different operating modes - Schneider, T.; Schulz, B.; Henke, C.; Witting, K.; Steenken, D.; Böcker, Joachim (2009 IEEE International Electric Machines and Drives Conference)

Optimal design of motor and gear for drives with high acceleration and load torque - Grotstollen, H. (2009 IEEE International Electric Machines and Drives Conference)

Optimal energy management for a hybrid energy storage system combining batteries and double layer capacitors - Romaus, C.; Böcker, Joachim; Witting, K.; Seifried, A.; Znamenshchykov, O. (2009 IEEE Energy Conversion Congress and Exposition)

Small-Signal Model and Control Design of LCC Resonant Converter with a Capacitive Load Applied in Very Low Frequency High Voltage Test System - Hu, M.; Fröhleke, N.; Böcker, Joachim (IEEE Energy Conversion Congress and Expo (ECCE), San Jose, USA, 2009)

Control Design for a Very Low-Frequency High-Voltage Test System - Cao, Z.; Fröhleke, N.; Böcker, Joachim (13th European Conference on Power Electronics and Applications (EPE2009), Barcelona, Spain)

Regular-sampled current measurement in AC drives using delta-sigma modulators - Peters, W.; Schulz, B.; Mathapati, S.; Böcker, Joachim (13th European Conference on Power Electronics and Applications, Barcelona, Spain)

Frequency / duty cycle control of LCC resonant converter supplying high voltage very low frequency test systems - Hu, M.; Fröhleke, Norbert; Böcker, Joachim (13th European Conference on Power Electronics and Applications (EPE2009), Barcelona, Spain)

Converter and control design for very low-frequency high-voltage test systems - Cao, Z.; Fröhleke, N.; Böcker, Joachim (IEEE Energy Conversion Congress and Expo (ECCE), San Jose, USA)

Design of a Resonant Converter for Very Low-Frequency High-Voltage Test Systems - Cao, Z.; Fröhleke, N.; Böcker, Joachim (Proc. of the PCIM China Conference, Shanghai, 2009)

Adaptive digital slope compensation for peak current mode control - Grote, T.; Schafmeister, Frank; Figge, H.; Fröhleke, N.; Ide, P.; Böcker, Joachim (2009 IEEE Energy Conversion Congress and Exposition)

Probabilistic planning integrated in a multi-level dependability concept for mechatronic systems - Klöpper, Benjamin; Sondermann-Wölke, Christoph; Romaus, Christoph; Vöcking, Henner (2009 IEEE Symposium on Computational Intelligence in Control and Automation)

Investigation of Power Supplies for a Piezoelectric Brake Actuator in Aircrafts - Li, Rongyuan; Fröhleke, Norbert; Wetzel, Hermann; Böcker, Joachim (2006 CES/IEEE 5th International Power Electronics and Motion Control Conference)

On the control bandwidth of servo drives - Böcker, Joachim; Beineke, S.; Bähr, A. (13th European Conference on Power Electronics and Applications (EPE2009), Barcelona, Spain)

Entwurf schwach gedämpfter piezoelektrischer Ultraschallsysteme - Kauczor, Christopher

A multi-objective approach to the design of low thrust space trajectories using optimal control - Dellnitz, M.; Ober-Blöbaum, Sina; Post, M.; Schütze, O.; Thiere, B. (Celestial Mechanics and Dynamical Astronomy)

The Jacobi-Maupertuis principle in variational integrators - Nair, S.; Ober-Blöbaum, Sina; Marsden, J.E. (7th International Conference of Numerical Analysis and Applied Mathematics)

Application of discrete mechanics and optimal control to spacecraft in non-Keplerian motion around small solar systems - Gehler, M.; Ober-Blöbaum, Sina; Dachwald, B. (Procceedings of the 60th International Astronautical Congress)

Optimization of spacecraft trajectories: a method combining invariant manifold techniques and descrete mechanics and optimal - Moore, A.; Ober-Blöbaum, Sina; Marsden, J.E. (19th AAS/AIAA Space Flight Mechanics Meeting)

Optimal control of gravity tractor spacecraft near arbitrarily shaped asteroids - Gehler, M.; Ober-Blöbaum, Sina; Dachwald, B.; Marsden, J.E. (1st IAA Planetary Defense Conference: Protecting Earth from Asteroids)

ATPG-Based Grading of Strong Fault-Secureness - Hunger, Marc; Hellebrand, Sybille; Czutro, Alejandro; Polian, Ilia; Becker, Bernd (15th IEEE International On-Line Testing Symposium (IOLTS'09)

Are Robust Circuits Really Robust? - Hellebrand, Sybille; Hunger, Marc (24th IEEE International Symposium on Defect and Fault Tolerance in VLSI Systems (DFT'09), (Invited Talk))

Robustheitsanalyse stark fehlersicherer Schaltungen mit SAT-basierter Testmustererzeugung - Hunger, Marc; Hellebrand, Sybille; Czutro, Alexander; Polian, Ilia; Becker, Bernd (3. GMM/GI/ITG-Fachtagung "Zuverlässigkeit und Entwurf")

Accurate RTOS Modelling and Analysis with SystemC - Zabel, Henning; Müller, Wolfgang; Gerstlauer, Andreas (Hardware Dependent Software - Principles and Practice)
Today, mobile and embedded real-time systems have to cope with the migration and allocation of multiple software tasks running on top of a real-time operating system (RTOS) residing on one or several system processors. Each RTOS has to be configured towards the individual needs of the application and environment. For this, different scheduling strategies and task priorities have to be evaluated in order to keep execution and response times for a given task set. Abstract RTOS simulation is applied to analyze different parameters in early design phases. This chapter presents a SystemC RTOS library for abstract yet accurate RTOS sim- ulation, supporting modeling of preemption in the presence of prioritized and nested interrupts. After introducing basic principles of abstract RTOS simula- tion, we present our SystemC library in detail. Thereafter, we discuss related approaches and close with applications in electronic automotive systems design and some evaluations.
Keywords: RTOS Modelling; RTOS Simulation; SystemC; Task Scheduling; Interrupt Analysis

Hardware-dependent Software - Introduction and Overview - Ecker, Wolfgang; Müller, Wolfgang; Dömer, Rainer (Hardware Dependent Software - Principles and Practice)
Rapidly rising system complexity has created a growing productivity gap in the design of electronic systems. One critical component is Hardware-dependent Software (HdS), the importance of which is often underestimated. In this chap- ter, we introduce HdS and illustrate its role in the overall system design context. We also provide a brief overview and define a basic HdS terminology and con- clude with a brief outlook over the following chapters in this book.
Keywords: Hardware-dependent Software; Systems Complexity; Productivity Gap

A UML Frontend for IP-XACT-based IP Management - Schattkowsky, Tim; Xie, Tao; Müller, Wolfgang (Proceedings of DATE'09)
IP-XACT is a well accepted standard for the exchange of IP components at Electronic System and Register Transfer Level. Still, the creation and manipulation of these descriptions at the XML level can be time-consuming and error-prone. In this paper, we show that the UML can be consistently applied as an efficient and comprehensible frontend for IP-XACT-based IP description and integration. For this, we present an IP-XACT UML profile that enables UML-based descriptions covering the same information as a corresponding IP-XACT description. This enables the automated generation of IP-XACT component and design descriptions from respective UML models. In particular, it also allows the integration of existing IPs with UML. To illustrate our approach, we present an application example based on the IBM PowerPC Evaluation Kit.
Keywords: Unified modeling language; XML; Power system modeling; Application software; Master-slave; Power system management; Acceleration; Scattering; Software engineering; Software standards

Increased Accuracy through Noise Injection in Abstract RTOS Simulation - Zabel, Henning; Müller, Wolfgang (Proceedings of DATE'09)
Today, mobile and embedded real-time systems have to cope with the migration and allocation of multiple software tasks running on top of a real-time operating system (RTOS) residing on one or multiple system processors. Abstract RTOS simulations and timing analysis applies for fast and early estimation to configure it towards the individual needs of the application and environment. In this context, a high accuracy of the simulation compared to an instruction set simulation (ISS) is of key importance. In this paper, we investigate the accuracy of abstract RTOS simulation and compare it to ISS and the behavior of the physical system. We show that we can reach an increased accuracy of the simulation when we inject noise into the time model. Our results indicate that it is sufficient to inject uniformly distributed random time values to the RTOS real-time clock.
Keywords: Timing; Analytical models; Clocks; Performance analysis; Scheduling; Operating systems; Delay; Real time systems; Application software; Context modeling

Development of Automotive Communication Based Real-Time Systems - A Steer-by-Wire Case Study - Klobedanz, Kay; Kuznik, Christoph; Elfeky, Ahmed; Müller, Wolfgang (Proceedings of IESS09)
Safety-critical automotive systems must fulfill hard real-time constraints to guarantee their reliability and safety requirements. In the context of network-based electronics systems, high-level timing requirements have to be carefully mastered and traced throughout the whole development process. In this paper, we outline the management of scheduling-specific timing information by the application of a steer-by-wire design example. We apply the principles of the AUTOSAR-compliant Timing Augmented Description Language (TADL) following the methodology introduced by the TIMMO project[2]. Focus of the example will be the identification of end-to-end timing constraints and their refinement by means of stimuli-response event chains.
Keywords: Abstraction Level Controller Area Network High Abstraction Level Event Chain Automotive System

Integration abstrakter RTOS-Simulation in den Entwurf eingebetteter automobiler E/E-Systeme - Becker, Markus; Zabel, Henning; Müller, Wolfgang

Systematic Model-in-the-Loop Test of Embedded Control Systems - Krupp, Alexander; Müller, Wolfgang (Proceedings of IESS09)

Hardware-dependent Software for Multi- and Many-Core Embedded Systems - Doemer, R.; Gerstlauer, A.; Müller, Wolfgang (Proceedings of ASP-DAC'09)

ON THE LONG TIME BEHAVIOR OF FREE STOCHASTIC SCHRÖDINGER EVOLUTIONS - Bassi, Angelo; Dürr, Detlef; Kolb, Martin (Reviews in Mathematical Physics)
We discuss the time evolution of the wave function which is the solution of a stochastic Schrödinger equation describing the dynamics of a free quantum particle subject to spontaneous localizations in space. We prove global existence and uniqueness of solutions. We observe that there exist three time regimes: the collapse regime, the classical regime and the diffusive regime. Concerning the latter, we assert that the general solution converges almost surely to a diffusing Gaussian wave function having a finite spread both in position as well as in momentum. This paper corrects and completes earlier works on this issue.

112Gb/s PolMux RZ-DQPSK with Fast Polarization Tracking Based on Interference Control - Wernz, H.; Bayer, S.; Olsson, B. E.; Camera, M.; Griesser, H.; Fuerst, C.; Koch, B.; Mirvoda, V.; Hidayat, A.; Noé, Reinhold (OFC: 2009 CONFERENCE ON OPTICAL FIBER COMMUNICATION, VOLS 1-5)

Multiplier-Free Real-Time Phase Tracking for Coherent QPSK Receivers - Hoffmann, Sebastian; Peveling, Ralf; Pfau, Timo; Adamczyk, Olaf; Eickhoff, Ralf; Noé, Reinhold (IEEE PHOTONICS TECHNOLOGY LETTERS)

Realization of Digital Coherent Receivers - Noé, Reinhold; Rueckert, Ulrich; Hoffmann, Sebastian; Pfau, Timo; Peveling, Ralf (2009 IEEE LEOS ANNUAL MEETING CONFERENCE PROCEEDINGS, VOLS 1AND 2)

Algorithms for Optical QAM Detection - Pfau, Timo; Noé, Reinhold (2009 DIGEST OF THE LEOS SUMMER TOPICAL MEETINGS)

Multiplier-Free Realtime Phase Tracking in Digital Synchronous QPSK Receiver for Coherent Optical Detection - Hoffmann, S.; Herath, V.; El-Darawy, M.; Pfau, T.; Woerdehoff, C.; Peveling, R.; Rueckert, U.; Noé, Reinhold (2009 INTERNATIONAL CONFERENCE ON INDUSTRIAL AND INFORMATION SYSTEMS)

Towards Real-Time Implementation of Coherent Optical Communication - Pfau, T.; Peveling, R.; Herath, V.; Hoffmann, S.; Woerdehoff, C.; Adamczyk, O.; Porrmann, M.; Noé, Reinhold (OFC: 2009 CONFERENCE ON OPTICAL FIBER COMMUNICATION, VOLS 1-5)

Realtime Phase Tracking with Multiplier-Free Barycenter Approximation in Digital Synchronous QPSK Receiver for Coherent Detection - Hoffmann, S.; El-Darawy, M.; Pfau, T.; Woerdehoff, C.; Peveling, R.; Rueckert, U.; Noé, Reinhold (2009 IEEE LEOS ANNUAL MEETING CONFERENCE PROCEEDINGS, VOLS 1AND 2)

Real-time Implementation of Digital Coherent Detection - Noé, Reinhold; Rueckert, U.; Hoffmann, S.; Peveling, R.; Pfau, T.; El-Darawy, M.; Al-Bermani, A. (2009 35TH EUROPEAN CONFERENCE ON OPTICAL COMMUNICATION (ECOC))

Optical time-of-flight measurement based on data transmission in a ring oscillator - Noé, Reinhold; Koch, Benjamin; Sandel, David (OPTICS EXPRESS)

Hardware-Efficient Coherent Digital Receiver Concept With Feedforward Carrier Recovery for M-QAM Constellations - Pfau, Timo; Hoffmann, Sebastian; Noé, Reinhold (JOURNAL OF LIGHTWAVE TECHNOLOGY)

38-krad/s 3.8-Grad Broadband Endless Optical Polarization Tracking Using LiNbO3 Device - Noé, Reinhold; Koch, Benjamin; Mirvoda, Vitali; Hidayat, Ariya; Sandel, David (IEEE PHOTONICS TECHNOLOGY LETTERS)